Pitfalls of compound interest effect: Private investors underestimate loss risks of financial products - Christian Zankiewicz (DIW Economic Bulletin, 2014)
People are investing their life savings in financial products, for instance, to provide for their retirement, and in doing so they are making their future financial situation almost entirely dependent on the success of these investments. The financial sector promotes numerous investment opportunities with widely varying levels of risk - from the classic private pension insurance to high-risk equity funds. To assist investors in selecting a product suitable for them and to safeguard against financial losses, policy-makers have prescribed standardized and comprehensible product leaflets and consulting protocols. But is that enough? In order to prevent investors from making poor investment decisions, they also need sufficient knowledge of the financial issues, which, for example, allow them to accurately assess the effects of compound interest on an investment and the risk of loss. This seems to be the problem area, as indicated by the results of a behavioral experiment conducted by DIW Berlin in cooperation with Humboldt-University Berlin: most of the participants chosen misunderstood the effect of compound interest - and therefore seriously underestimated the investment risk.
Keywords: C91; D3; D14; G2; 330; behavioral economics; irrational expectations; binomial tree